Implementasi Multifactor Evaluation Process (MFEP) Pada Pemilihan Foundation Bagi Perias Pemula - Mawaddah Anjelita; Eka Irawan; Agus Perdana Windarto; Dedy Hartama; Irfan Sudahri Damanik (STMIK Budi Darma, 2020)
Abstract−This study aims to provide input, especially for novice make-up in choosing the best foundation, considering that foundation is one of the main components in make-up which is very influential in the perfection of make-up. The algorithm used in this study is the Multifactor Evaluation Process (MFEP). There are 5 factors used in the selection foundation, namely the durability of the foundation, the age of the product, the price, the color variants presented, and the coverage or ability of the foundation to cover deficiencies in the face. The foundation products used in this research are Lt-Pro Smooth Corector, Kryolan, Ultima II, Naturactor, and Este Lauder. The implementation of the Multifactor Evaluation Process (MFEP) in the selection of foundations for beginners can be applied. The result was that Kryolan foundation could be an alternative for beginners who were confused in choosing a foundation. The second order was obtained by Naturactor Foundation.Keywords: MFEP, Decision Support System, Multifactor Evaluation Process, Selection of Foundation, SPK